Early metabolic response to acute myocardial ischaemia in patients undergoing elective coronary angioplasty. Issue 1 (10th March 2018) - Di Marino, Sara; Viceconte, Nicola; Lembo, Angelo; Summa, Vincenzo; Tanzilli, Gaetano; Raparelli, Valeria; Truscelli, Giovanni; Mangieri, Enrico; Gaudio, Carlo; Cicero, Daniel Oscar
Abstract : Objective: Balloon-induced transient coronary ischaemia represents a model of myocardial ischaemia and reperfusion. We are interested in the very early systemic metabolic response to this event. Methods: Blood samples of patients with stable angina (SA) were collected before and after coronary angioplasty. Serum metabolic profiles were obtained using nuclear magnetic resonance spectroscopy. Univariate and multivariate analyses were used to investigate changes in metabolite concentrations. Results: Thirty-four consecutive patients with SA, undergoing elective coronary angioplasty at Policlinico Umberto I of Rome, were included in this study. Changes in metabolites concentration induced by balloon occlusion in venous and arterial sera were detected. In both serum types, a significant increase in ketone bodies, 2-hydroxybutyrate, glutamine and O-acetylcarnitine concentration is observed, while alanine, lactate, phenylalanine and tyrosine decreased after intervention. Most significant metabolic changes were detected in arterial serum. Conclusions: Our study points out two main global metabolic changes in peripheral blood after balloon-induced coronary ischaemia: ketone bodies increase and lactate decrease. Both could be related to compensation mechanisms finalised to fulfil heart's needs after short period of myocardial ischaemia and probably after reperfusion.